2020
DOI: 10.29333/pr/7845
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Utilization of ICT Facilities for Teaching Purposes among University Lecturers: Influence of Gender, Age, Qualification and Years of Teaching Experience

Abstract: This study investigates lecturers' level of utilization of ICT facilities for teaching purposes in Nigerian universities. A descriptive survey design was adopted for the study. And a questionnaire with a reliability of 0.907 was used for data collection. Data was collected at the Abubakar Tafawa Balewa University, Bauchi from a sample of 433 lecturers out of a population of 928. The results show that lecturers have the knowledge of using ICT facilities in teaching, however, they rarely use them in teaching. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
(37 reference statements)
1
6
1
Order By: Relevance
“…The success of ICT in education depends heavily on the digital competencies teachers acquire, their professional development, and the training provided to teachers (Yushau & Nannim, 2020). Among all these conditions are teachers' attitudes towards ICT, ICT skills, and training in relation to utilizing IT-based multimedia in the current educational environment.…”
Section: Identification Of Ict and Teaching Media Skills In Geography...mentioning
confidence: 99%
See 2 more Smart Citations
“…The success of ICT in education depends heavily on the digital competencies teachers acquire, their professional development, and the training provided to teachers (Yushau & Nannim, 2020). Among all these conditions are teachers' attitudes towards ICT, ICT skills, and training in relation to utilizing IT-based multimedia in the current educational environment.…”
Section: Identification Of Ict and Teaching Media Skills In Geography...mentioning
confidence: 99%
“…It is necessary to consider the tools applied in the classroom and teachers' experiences, habits, knowledge, and difficulties in applying learning technology. The following are the results of the identification of the teaching experience of geography teacher groups in Surakarta City and Karanganyar Regency: Source: Adopted from (Gutiérrez Martín et al, 2022); (Yusrizal et al, 2019); (Topchyan & Woehler, 2021); (Brooks, 2021); (Yushau & Nannim, 2020) and modified by the author.…”
Section: Identification Of Ict and Teaching Media Skills In Geography...mentioning
confidence: 99%
See 1 more Smart Citation
“…Communicative processes obviously and actively move to cyberspace (Owan, Ekpe & Eneje, 2020). Сyberspace represents the virtual social field of human life represented within the interaction of a computer, networks and a person; the appearance of cyberspace is caused by the set of the IT industry manifestations, creating new technologies of interpersonal interaction (Baryshev, 2008;Shaidullina et al, 2015;Minakhmetova et al, 2017;Sudakova et al, 2017;Mukhametshin et al, 2019;Razumovskaya et al, 2018Razumovskaya et al, , 2019Nurieva & Inozemtseva, 2020;Gimaliev et al, 2020;Yushau & Nannim, 2020;Valeeva, Baykova & Kusainov, 2016;Privalova et al, 2019). The main characteristics of cyberspace are coherence and informational content completeness, sociality -fullness of people images, which are supported by texts, video and audio information, images (Galiullina, 2018;Levina et al, 2019;Orekhovskaya et al, 2019;Khairullina et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Different results have been provided by diffeent scholars on the influence of gender on the use of an instructional resources such as google classroom. Islahi & Nasrin, (2018) found out that there is no significance difference in individual's use of information technology in relation to their gender while Yushau & Nannim, (2020) reported that there is a significant difference in male and females use of ICT facilities. It is normal to have different results as people's opinion varies from place to place due to difference in cultural background, political laws etc.…”
Section: Introductionmentioning
confidence: 99%